Is there a post-COVID urban model? The pandemic as a catalyst of urban transformations in Buenos Aires - Diego Ezequiel Vázquez; Martina Daniela Berardo (Íconos)
Since the beginnings of the COVID-19 pandemic, intellectuals and technical urban personnel across the world developed diagnostics and mediatic prophecies about the radical changes that cities would suffer and, particularly, spaces for public use. This text analyzes the urban changes that the Government of the City of Buenos Aires developed during the fourth period of the Republican Proposal Party (2019-2022), in response to the challenge of the pandemic. In addition, these changes are compared with the previous management of the same party between 2007 and 2019. The objective is to trace continuities and ruptures among the programs implemented, in relation to the rhetoric regarding public space, and in the urban planning used to design and justify urban policies. For this, a hybrid methodological design was developed that combines document, spatial, and cultural analysis. The methodological strategy was concentrated on the empirical production and descriptive and interpretative analysis of a documental body that included two main sources – publications from local government and from mass media. From the results it is evident that, before the conformation of a new post-COVID urban paradigm, local urban management during the pandemic was characterized by the deepening of existing transformations and urban models. Thus, the pandemic operated as a catalyst for changes that were already being developed.